Hubungan Self-Acceptance dengan Quarter-Life Crisis pada Generasi Z dalam Konteks Memilih Karier - Tetty Winda Siregar; Samuela Thena; Hally Weliangan (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Generation Z faces career challenges due to labor market changes and demands for financial independence, which may trigger a quarter-life crisis. This study aims to examine the relationship between self-acceptance and quarter-life crisis among Generation Z. A quantitative method was used with purposive sampling involving 117 respondents aged 20–29, with at least a high school education, and currently seeking or holding a job. The research instruments were the Quarter-life Crisis scale and the Unconditional Self-Acceptance Questionnaire. Pearson Product Moment analysis yielded r = -0.685**, p = 0.000, indicating a highly significant negative relationship between self-acceptance and quarter-life crisis.